One Hundred Years of Congenital Fibrinogen Disorders - Casini, Alessandro; Moerloose, Philippe de; Neerman-Arbez, Marguerite (Seminars in Thrombosis and Hemostasis, 2022)
Congenital fibrinogen disorders encompass a broad range of fibrinogen defects characterized by a wide molecular and clinical spectrum. From the first clinical description of afibrinogenemia in 1920, many major achievements have contributed to a better understanding of these complex disorders. The finding of causative mutations in all three fibrinogen genes has contributed to reveal the molecular mechanisms involved in biosynthesis of the fibrinogen molecule and to clarify the basic processes of fibrin polymerization and fibrinolysis. The compilation of abundant cases with detailed genetic, biological, and clinical features has enabled the classification of congenital fibrinogen disorders into several types and subtypes. Thus, the recent classification of congenital fibrinogen disorder is based not only on the clottable and antigenic fibrinogen levels but also on the patient's clinical phenotype and genotype. Fibrinogen supplementation is the cornerstone of bleeding management in fibrinogen disorders. Since the discovery of blood fractionation, the method of production of fibrinogen concentrate has been progressively modified to significantly improve purity and safety. Nevertheless, the availability of such products is still limited to a few countries and the optimal threshold of fibrinogen to target is still not established. In this review, we describe the major advances that have characterized 100 years of congenital fibrinogen disorders, focusing on afibrinogenemia and dysfibrinogenemia.
Keywords: afibrinogenemia; dysfibrinogenemia; fibrinogen